Alterations in default mode network connectivity during pain processing in borderline personality disorder - Klütsch, Rosemarie Christine; Schmahl, Christian; Bohus, Martin (Archives of general psychiatry, 2012)
Context: Recent neuroimaging studies have associated activity in the default mode network (DMN) with self-referential and pain processing, both of which are altered in borderline personality disorder (BPD). In patients with BPD, antinociception has been linked to altered activity in brain regions involved in the cognitive and affective evaluation of pain. Findings in healthy subjects indicate that painful stimulation leads to blood oxygenation level–dependent signal decreases and changes in the functional architecture of the DMN. Objectives: To connect the previously separate research areas of DMN connectivity and altered pain perception in BPD and to explore DMN connectivity during pain processing in patients with BPD. Design: Case-control study. Setting: University hospital. Participants: Twenty-five women with BPD, including 23 (92%) with a history of self-harm, and 22 age-matched control subjects. Interventions: Psychophysical assessment and functional magnetic resonance imaging during painful heat vs neutral temperature stimulation. Main: Outcome Measure Connectivity of DMN as assessed via independent component analysis and psychophysiological interaction analysis. Results: Compared with control subjects, patients with BPD showed less integration of the left retrosplenial cortex and left superior frontal gyrus into the DMN. Higher BPD symptom severity and trait dissociation were associated with an attenuated signal decrease of the DMN in response to painful stimulation. During pain vs neutral, patients with BPD exhibited less posterior cingulate cortex seed region connectivity with the left dorsolateral prefrontal cortex. Conclusions: Patients with BPD showed significant alterations in DMN connectivity, with differences in spatial integrity and temporal characteristics. These alterations may reflect a different cognitive and affective appraisal of pain as less self-relevant and aversive as well as a deficiency in the switching between baseline and task-related processing. This deficiency may be related to everyday difficulties of patients with BPD in regulating their emotions, focusing mindfully on 1 task at a time, and efficiently shifting their attention from one task to another.